Detecting Special Education Teachers' Emotions as To the Skills Workshops - Κουβαρά, Ελένη (Education Sciences, 2023)
Positive Psychology is the scientific study of human potential and virtues (Sheldon & King, 2001). It is the newest, fastest growing, innovative branch of Psychology and deals with understanding and enhancing well-being. Positive Psychology courses and seminars are widespread, which are taught in Universities (Seligman, 2002), however, informing the active educational staff is considered important for the optimization of the educational process. Positive emotions such as joy, contentment, interest and love evoke a sense of security (Fredrickson, Mancuso, Branigan & Tugade, 2000). Experiencing moments with positive emotions, the person is subjected to positive stimuli, enriched with skills, working with flexibility, curiosity and creativity. Positive and negative emotions are complementary and interrelated, with negative ones focusing on action and behavior and positive ones on gathering resources, building defenses, and acquiring essential life skills (Diener, Wirtz, Tov, Kim-Prieto, Choi, Oishi & Biswas-Diener, 2010). On the occasion of the educational upgrade, the Ministry of Education piloted the Skills Workshops in the 2020-2021 school year (Circular 94236/GD4/29-07-2021 Ministerial Decision (Β΄ 3567)). The purpose of the work was to detect the emotions of the Special Education Teachers in the schools where the Skills Workshops were implemented. Educators participated who a) implemented the program as a pilot in the 2020-2021 school year and b) implemented the program following their mandatory inclusion in the schools' Program Time Tables by the Ministry of Education. The Positive and Negative Affect Scale (PANAS) was the psychometric tool which was used.